KARAKTERISTIK BEBERAPA PARAMETER KUALITAS AIR (FISIKA-KIMIA) DI PERAIRAN PANGEMPANG KECAMATAN MUARA BADAK KUTAI KARTANEGARA - Muhammad Irfan; Jailani Jailani; Widya Kusumaningrum (Jurnal Tropical Aquatic Sciences, 2022)
To find out the characteristics of sea water quality in tidal and low conditions with parameters including DO, Salinity, pH, Temperature, Turbidity, Brightness. The study was conducted from February to April 2019. The collection of water quality parameters in pangempang waters using tools contained in the laboratory at 5 station points. Results from the parameters DO, Salinity, pH, Temperature and Brightness at the research site, while for Brightness in the Laboratory of Water Quality Faculty of Fisheries and Marine Sciences. The average result of the measurement at the tide conditions on the DO parameter is obtained 5.76 mg / l, the Salinity parameter obtained 21.8 o/oo, the pH parameter obtained 6.4, the temperature parameter obtained 32.2 oC, the turbidity parameter obtained 0.27 NTU parameter Brightness obtained 2.6 meters, while the average result of the measurement at receding conditions at the DO parameter obtained 6.56 mg / l, salinity parameter obtained 23.2 o/oo parameter pH obtained 7, Temperature parameter obtained 31.8oC turbidity parameter obtained 1.6 NTU parameter Brightness obtained 1.33 Meters.